New polycrystalline modeling as applied to textured steel sheets. (September 2017) - Chandola, Nitin; Cazacu, Oana; Revil-Baudard, Benoit
Highlights: New approach for modeling polycrystalline behavior. Constituent grains modeled with recent single-crystal criterion. Accurate prediction of r-values and yield stress anisotropy of textured steel sheets. Abstract: It has been long recognized that the preferred orientation of the grains, arising from processing of metallic materials, result in anisotropic plastic behavior. An accurate assessment of the resulting macroscopic plastic anisotropy is thus essential in predicting the mechanical performance of alloys. This paper presents a new approach for modeling polycrystalline behavior. A key aspect in the formulation is the use of the single-crystal yield criterion recently developed by Cazacu et al., 2017 for the description of the plastic properties of the constituent grains. The capabilities of the polycrystalline model in predicting the directionality of macroscopic tensile properties are illustrated by comparing the theoretical predictions with mechanical data on steel sheets of various textures. There is a good agreement between experimental and theoretical predictions.